Diagnostic, Therapeutic Predictive, and Prognostic Value of Neutrophil Extracellular Traps in Patients With Gastric Adenocarcinoma - Zhang, Yiyin; Hu, Yangyang; Ma, Cui; Sun, Hua; Wei, Xiaoli; Li, Min; Wei, Wei; Zhang, Fei; Yang, Feng; Wang, Hua; Gu, Kangsheng (Frontiers in Oncology, 2020)
Neutrophils are a significant population of infiltrated immune cells in the tumor microenvironment. Neutrophil extracellular traps (NETs) are implicated in the biological behavior of many malignant tumors. NETs can be degraded into soluble nucleosomes, leading to the release of fragments containing DNA and granule proteins into the peripheral blood (PB). Using human gastric cancer (GC) biopsies and PB samples, we investigated the specific value of NETs in GC from a clinical perspective. In summary, the formation of NETs was discovered in the tissue microenvironment and PB of GC patients. The amounts of NETs and neutrophil accumulation decreased from tumor tissue to paratumor tissue. In addition, the level of NETs in the PB gradually declined through the following patient populations: advanced disease patients, preoperative patients, postoperative patients, benign disease patients, and healthy controls. The levels of NETs in the plasma and serum were significantly correlated. As a serum biomarker, NETs had a better diagnostic value than carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) in GC. The neutrophil count and neutrophil to lymphocyte ratio (NLR) were significantly associated with the level of NETs in the PB. The existence of lymph node metastasis indicated a high level of NETs in the serum. Moreover, the level of NETs in the PB was inversely correlated with short-term efficacy in GC patients who had received advanced first-line treatment. The higher baseline level of NETs in the PB of patients with negative HER2 status was correlated with worse progression-free survival (PFS). And the level of NETs in the PB was a unfavorable independent prognostic factor for PFS in patients with advanced GC who had received first-line treatment. Thus, NETs have novel diagnostic, therapeutic predictive, and prognostic value in GC patients.